Propagation of positive effects of postdisaster policies through supply chains evidence from the Great East Japan earthquake and tsunami. - Kashiwagi, Yuzuka (Economic working papers., 2020)
A positive effect of the subsidies on small recipient firms postdisaster sales and employment was found in the study. There was also a positive indirect effect of the group subsidies on firms in disaster-hit prefectures that did not receive any group subsidy but were linked through supply chains with a recipient firm. The results indicate the propagation of postdisaster policy effects through supply chains.